2019
DOI: 10.1177/2325967118825294
|View full text |Cite
|
Sign up to set email alerts
|

The Middle and Distal Aspects of the Ulnar Footprint of the Medial Ulnar Collateral Ligament of the Elbow Do Not Provide Significant Resistance to Valgus Stress: A Biomechanical Study

Abstract: Background:The medial ulnar collateral ligament (UCL) insertion of the elbow has been shown to extend distally beyond the sublime tubercle. The contribution to valgus stability of the distal aspect of the footprint is unknown.Purpose/Hypothesis:The purpose of this study was to determine the contribution of each part of the UCL footprint to the elbow valgus stability provided by the UCL. It was hypothesized that the distal two-thirds of the ulnar UCL footprint would not contribute significantly to valgus stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…1,16,19,26,27,30,35 Reconstruction with ulnar tunnels at all 3 tunnel locations (5, 10, and 15 mm from the ulnohumeral joint line) successfully restored medial elbow stability across all angles of flexion, and there were no significant differences in torque to failure among the 3 tunnel locations. Erickson et al 12 recently published biomechanical data demonstrating the relative contribution of the proximal, middle, and distal thirds of the mUCL ulnar footprint and found that only release of the proximal third resulted in increased valgus rotation. While the proximal third of the ligament plays a key role in stability in a native ligament, as Erickson et al 12 recently quantified, the results of our study demonstrate that reconstruction that places the distal fixation within up to 15 mm of the ulnotrochlear joint line can restore valgus stability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,16,19,26,27,30,35 Reconstruction with ulnar tunnels at all 3 tunnel locations (5, 10, and 15 mm from the ulnohumeral joint line) successfully restored medial elbow stability across all angles of flexion, and there were no significant differences in torque to failure among the 3 tunnel locations. Erickson et al 12 recently published biomechanical data demonstrating the relative contribution of the proximal, middle, and distal thirds of the mUCL ulnar footprint and found that only release of the proximal third resulted in increased valgus rotation. While the proximal third of the ligament plays a key role in stability in a native ligament, as Erickson et al 12 recently quantified, the results of our study demonstrate that reconstruction that places the distal fixation within up to 15 mm of the ulnotrochlear joint line can restore valgus stability.…”
Section: Discussionmentioning
confidence: 99%
“…Erickson et al 12 recently published biomechanical data demonstrating the relative contribution of the proximal, middle, and distal thirds of the mUCL ulnar footprint and found that only release of the proximal third resulted in increased valgus rotation. While the proximal third of the ligament plays a key role in stability in a native ligament, as Erickson et al 12 recently quantified, the results of our study demonstrate that reconstruction that places the distal fixation within up to 15 mm of the ulnotrochlear joint line can restore valgus stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,13 Furthermore, only the proximal-most portion of the UCL insertion onto the sublime tubercle of the ulna contributes significantly to valgus stability of the elbow, indicating that there is a large amount of stress seen by a small area of the distal UCL insertion. 10 This is in contrast to the proximal insertion where the load is dispersed throughout the entire footprint. 13 However, during UCLR a distal tunnel and proximal socket are created and a graft is used to reconstruct the UCL.…”
Section: Discussionmentioning
confidence: 99%
“…Cadaveric studies have described the origin of this ligament to have a mean footprint of 45.5 mm 2 on a flat portion of the humerus, 13.4 mm anteroinferior to the most prominent portion of the medial epicondyle. 11,13 The ligament spans an average length of 53.9 mm distally and has a central insertion onto the sublime…”
Section: Anatomic Considerationsmentioning
confidence: 99%